Urinary biomarkers of acute kidney injury in deceased organ donors – kidney injury molecule‐1 as an adjunct to predicting outcome. (3rd June 2014) - Field, Melanie; Dronavalli, Vamsi; Mistry, Punam; Drayson, Mark; Ready, Andrew; Cobbold, Mark; Inston, Nicholas
Abstract Background Deceased kidney donors are increasingly "marginal, " and many have risk factors for acute kidney injury (AKI) that may impact on subsequent renal transplant outcome. Despite this, determining the presence of AKI at the time of deceased organ donation remains difficult. Methods Urine samples from 182 brainstem dead multi‐organ donors (all of whom donated hearts that were transplanted) were analyzed for a Luminex™ panel of biomarkers linked with AKI. This included KIM‐1, NGAL, IFN‐γ, TNF‐α, cystatin C, Fractalkine and vascular endothelial growth factor. Levels were correlated to early renal transplant outcomes, most specifically delayed graft function. Results Donor urinary KIM‐1 levels were significantly higher in donors whose kidneys displayed aberrant early function (p = 0.011). Fractalkine levels showed a trend toward elevation in such donors but uncorrected this did not attain significance. No correlation occurred with the remaining biomarkers. Conclusions KIM‐1 appears to show promise as a marker for AKI in deceased cardiac organ donors. The availability of a lateral flow device (Renastick™) for KIM‐1 that also demonstrates higher urinary KIM‐1 levels in donors whose kidneys show aberrant initial function (p = 0.03), makes KIM‐1 a potential indicator of AKI that may merit further evaluation for its application at the donor bedside.